Analysis of the Implementation of the Tuberculosis (TBC) Elimination Program in Makassar City, Indonesia - Andi Rezky Aulia Amiruddin; Andi Surahman Batara; Abdul Gafur (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study analyzes the implementation of the Tuberculosis (TBC) Elimination Program in Makassar City using the policy implementation frameworks of Van Meter and Van Horn and George C. Edwards III. Research Method: A qualitative design with domain analysis was employed. Data were collected through interviews, observations, and document reviews at the Makassar City Health Office and three community health centers. Results and Discussion: The program has generally been implemented according to established policy standards. However, implementation remains constrained by limited human resources, weak cross-sectoral coordination, community stigma, and patients' economic constraints. Policy standards, communication, bureaucratic structure, implementer commitment, and infrastructure have supported implementation. Strengthening human resources, cross-sectoral collaboration, and community education is necessary to accelerate tuberculosis elimination. Implications: The findings support policymakers in strengthening human resources, collaboration, and community-based TB control strategies. Originality: This study integrates the policy implementation frameworks of Van Meter and Van Horn and George C. Edwards III to analyze the implementation of the Tuberculosis Elimination Program in Makassar City.